Patient satisfaction of primary care services in Gulf Cooperation Council Countries: A scoping review - Abdulaziz Alhenaidi; Waleed Al Nadabi; Asmaa Al‐Haqan; Hisham Kelender (Journal of General and Family Medicine, 2023)
Abstract Patient satisfaction (PS) is an essential element in evaluating and improving healthcare systems. Few studies have gathered evidence about patient satisfaction with primary care (PC) services in the Gulf Cooperation Council (GCC) countries. Therefore, it is important to review the existing literature examining PS with PC services in the GCC countries. This scoping review was conducted for primary data studies published between 2000 to March 2022. Out of 4461 screened articles, 37 met the inclusion criteria. Most studies were conducted in Saudi Arabia and were of cross sectional methodology. PS with primary care in the GCC is affected by multiple provider‐related and patient‐related factors and users are generally satisfied with the service provided. Future research should focus on the effects of the factors that were not explored and validate the existing results.